2005
DOI: 10.1128/jvi.79.14.9296-9300.2005
|View full text |Cite
|
Sign up to set email alerts
|

Growth Suppression Induced by Downregulation of E6-AP Expression in Human Papillomavirus-Positive Cancer Cell Lines Depends on p53

Abstract: The ubiquitin-protein ligase E6-AP is utilized by the E6 oncoprotein of human papillomaviruses (HPVs) associated with cervical cancer to target the tumor suppressor p53 for degradation. Here, we report that downregulation of E6-AP expression by RNA interference results in both the accumulation of p53 and growth suppression of the HPV-positive cervical cancer cell lines HeLa and SiHa. In addition, HeLa cells, in which p53 expression was suppressed by RNA interference, are significantly less sensitive to the dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 27 publications
(26 reference statements)
5
43
1
Order By: Relevance
“…Furthermore, four copies of BS2, upstream of a minimal promotor, were sufficient to confer transcriptional activation (BS2), whereas mutation of these sites (BS2Mut) resulted in loss of responsiveness ( Figure 1b). In further support for the p53-dependence of the PUMA induction, we did not observe an increase in PUMA transcript levels or promoter activities upon E6 inhibition in HeLa cells in which p53 expression is suppressed by RNAi (Hengstermann et al, 2005) (data not shown). These results show that the transcriptional activities of endogenous p53 are restored upon RNAi-mediated E6 inhibition in HeLa cells and induce the PUMA promoter via its p53 recognition sites.…”
Section: Induction Of Puma Following Inhibition Of E6 Expressionsupporting
confidence: 54%
See 3 more Smart Citations
“…Furthermore, four copies of BS2, upstream of a minimal promotor, were sufficient to confer transcriptional activation (BS2), whereas mutation of these sites (BS2Mut) resulted in loss of responsiveness ( Figure 1b). In further support for the p53-dependence of the PUMA induction, we did not observe an increase in PUMA transcript levels or promoter activities upon E6 inhibition in HeLa cells in which p53 expression is suppressed by RNAi (Hengstermann et al, 2005) (data not shown). These results show that the transcriptional activities of endogenous p53 are restored upon RNAi-mediated E6 inhibition in HeLa cells and induce the PUMA promoter via its p53 recognition sites.…”
Section: Induction Of Puma Following Inhibition Of E6 Expressionsupporting
confidence: 54%
“…The specific targeting of E6-encoding transcripts by RNAi results in an increase in p53 levels and the induction of apoptosis in HPV16 or HPV18-positive cancer cells (Butz et al, 2003;Hengstermann et al, 2005;Kelley et al, 2005). Apoptosis, as induced by inhibition of E6 expression (in the following termed 'E6 inhibition'), appears to be p53-dependent, because HeLa cells, in which p53 expression was stably suppressed by RNAi, become resistant to siRNAs against E6 (Hengstermann et al, 2005).…”
Section: Induction Of Puma Following Inhibition Of E6 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…E6's inactivation of human p53 has been argued to be E6AP dependent based upon the use of antisense oligomers (Traidej et al, 2000), a dominant-negative E6AP (Talis et al, 1998) and small interfering RNAs (siRNAs) (Hengstermann et al, 2001(Hengstermann et al, , 2005Kelley et al, 2005). In particular, siRNA-mediated knockdown of E6AP in HPV16-positive cervical cancer-derived cell lines resulted in the same upregulation of p53-responsive genes as seen with E6 siRNAs (Kelley et al, 2005;Nomine et al, 2006).…”
Section: E6ap Is Not Required For E6's Inactivation Of Mouse P53mentioning
confidence: 99%